Pelatihan dan Pendampingan Penerapan Inquiry-Based Learning Untuk Meningkatkan Kreativitas Guru dan Siswa - Sakdiah Wati; Mustofa Mustofa (Universitas Negeri Gorontalo, 2026)
Strengthening teachers' competence in implementing student-centered learning is essential for supporting the implementation of the Merdeka Curriculum. However, Indonesian language instruction at MI Firqoniah and MTs Furqoniyah Gandus was still predominantly conducted using conventional teaching approaches, limiting students' active participation and creativity. This community service program aimed to improve teachers' understanding, skills, and readiness to implement Inquiry Based Learning in Indonesian language instruction. The program employed a participatory approach consisting of preparation, training sessions, discussions, lesson planning workshops, mentoring, evaluation, and follow-up activities. The program was conducted on 20–21 June 2025 and involved 25 teachers from MI Firqoniah and MTs Furqoniyah Gandus. Evaluation was carried out using a qualitative descriptive approach through observation, documentation, and reflective discussions focusing on participants' attendance, engagement, conceptual understanding, lesson-planning skills, and readiness to implement Inquiry Based Learning. The results indicated that all participants actively engaged in the program, demonstrated a clear understanding of the concepts and instructional procedures of Inquiry Based Learning, successfully developed inquiry-based lesson plans, and expressed readiness to apply the approach in Indonesian language classrooms. The program contributed to strengthening teachers' pedagogical competence in designing more active, innovative, and student-centered learning while providing a foundation for sustainable professional mentoring within schools.